Space concept of the interior of the traditional Toba Batak house (a case study in the Toba Samosir regency in North Sumatra, Indonesia) / Pantas Pitara Pangoloi Lumban Tobing - Lumban Tobing, Pantas Pitara Pangoloi (2007)
The Batak people nowadays seldom build the traditional house. Moreover many of the old traditional buildings were left behind without caring for maintenance. They lived in a new modern house. The main purpose of this study is: To identify and analyze the interior space concept of the Toba Batak traditional house in 18th century and the interior space concept at present and then compared the two of it to know the change of space concept in the years went by. At first the researcher studied the 18th century Toba Batak house from literature, to know the 18th century concept of Toba Batak interior design. This research was a case study that based on field survey held in the area of Toba Samosir Regency. The location of the field research were 24 huta / villages in Toba Samosir by the Toba Lake. The samples were 30 traditional houses of jabu ruma and jabu sopo in 24 huta. The samples must had been built around 100 years or more. In that area also distributed 110 exemplars of questionnaires to the inhabitant of the traditional architecture. All the data processed and the researcher found that: 1. The people of Toba Batak in the 18th century had the ability to "see" the intangible wall/partition, with their mental set, mind and soul. 2. In the old days the traditional building was the whole house, at present it was only part of the whole house. 3. The old house was a big room, single room, mono-room, but later changed to multi rooms. 4. There was a change of view on space concept for the dwelling. It was recommended to restore the huta /village environment. Designers recommended to redesign the interior of the traditional form to make it more suitable to the present need for the people.